Public debt and the effects of government expenditure on private consumption - A Kalman filter analysis of the Swedish experience 1970-1997 - Martin Johansson; Kristian Jönsson (Lund University, School of Economics and Management, Department of Economics, 2003)
Recently, it has been suggested that the effect of government expenditure on private consumption is dependent on the level of public debt. More specifically, a higher public debt implies a less Keynesian response in private consumption. In this paper we investigate if this theory is supported by Swedish data 1970-1997 by estimating a consumption function allowing for time-varying parameters. Our main finding is that the effect of government expenditure has become less Keynesian over time. This coincides with a large increase in public debt, lending support to the theoretical predictions.
Keywords: E12; E21; E62; 330; Government expenditure; private consumption; time-varying parameters